2022
DOI: 10.3390/medicina58121734
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Expression Patterns of Genes Coding for Biological Response Modifiers Involved in Inflammatory Responses and Development of Fibrosis in Chronic Hepatitis C: Upregulation of SMAD-6 and MMP-8 and Downregulation of CAV-1, CTGF, CEBPB, PLG, TIMP-3, MMP-1, ITGA-1, ITGA-2 and LOX

Abstract: Background and Objectives: The aim of this study was to analyze the expression of genes on transcriptomic levels involved in inflammatory immune responses and the development of fibrosis in patients with chronic hepatitis C. Materials and Methods: Expression patterns of 84 selected genes were analyzed with real-time quantitative RT PCR arrays in the peripheral blood of treatment-naive patients with chronic hepatitis C and healthy controls. The panel included pro- and anti-fibrotic genes, genes coding for extra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Not only that, RAF1 also contributes to vascular endothelium homeostasis and cardiac remodeling after myocardial infarction [21]. CEBPB plays a critical role in the regulation of immune and in ammatory responses [22]. Several studies have demonstrated that CEBPB is involved in the pathogenesis of myocardial infarction [23].…”
Section: Discussionmentioning
confidence: 99%
“…Not only that, RAF1 also contributes to vascular endothelium homeostasis and cardiac remodeling after myocardial infarction [21]. CEBPB plays a critical role in the regulation of immune and in ammatory responses [22]. Several studies have demonstrated that CEBPB is involved in the pathogenesis of myocardial infarction [23].…”
Section: Discussionmentioning
confidence: 99%
“…Loss of MMP‐8 impaired inflammatory response and increased the risk of skin tumors in mice (Balbín et al, 2003), but its effect on liver fibrosis is unknown. On the other hand, overexpression of MMP‐8 reduced fibrosis and induced breakdown of fibrous tissues in a rat model of live fibrosis induced by CCl 4 or BDL (Harty et al, 2005; Radmanić et al, 2022). Therefore, the increased expression of MMP‐8 in alcoholic cirrhosis may be a self‐defense mechanism to alleviate liver fibrosis, and MMP‐8 may be a promising therapeutic target to reduce the risk of cancer and liver fibrosis.…”
Section: Pathophysiology Of Liver Fibrosismentioning
confidence: 99%